2013
DOI: 10.1097/01.csmr.0000434106.12813.69
|View full text |Cite
|
Sign up to set email alerts
|

Training the Developing Brain, Part I

Abstract: Based on the fundamental principles of pediatric exercise science and developmental physiology, childhood provides a critical window to develop the physical readiness of youth through age-related training programs that are designed purposely to teach and reinforce fundamental movement skills to enhance preparedness for physical activity and sport. Successful implementation of developmental programs requires age-related instruction by qualified professionals who understand the physical and psychosocial uniquene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…Instead, pre-pubertal children should be prescribed a resistance 412 training program that focuses on enhancing muscle strength, function and control due to the 413 high degree of plasticity in neuromuscular function during this developmental period [32,45]. 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Furthermore, the importance of having fun in a supportive environment should not be …”
mentioning
confidence: 99%
“…Instead, pre-pubertal children should be prescribed a resistance 412 training program that focuses on enhancing muscle strength, function and control due to the 413 high degree of plasticity in neuromuscular function during this developmental period [32,45]. 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Furthermore, the importance of having fun in a supportive environment should not be …”
mentioning
confidence: 99%
“…Specific to injury prevention, there is emerging evidence that indicates neuromuscular training implemented at earlier ages is most effective in the reduction of traumatic knee injury [23]. It has been suggested that cognitive developmental considerations are also critical to optimize integrative neuromuscular training for youth [24]. Specifically it is required that instructors acknowledge and address the varying attentive abilities of young athletes [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cognitive developmental considerations are also critical to optimize integrative neuromuscular training for youth [24]. Specifically it is required that instructors acknowledge and address the varying attentive abilities of young athletes [24]. For example, Hicks law describes that the more choices an individual has, the longer it takes to make a decision [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations